DNA adducts in urothelial cells: relationship with biomarkers of exposure to arylamines and polycyclic aromatic hydrocarbons from tobacco smoke - Vineis, Paolo; Talaska, Glenn; Malaveille, Christian; Bartsch, Helmut; Martone, Tiziana; Sithisarankul, Pornchai; Strickland, Paul (International journal of cancer, 1996)
Markers of exposure to polycyclic aromatic hydrocarbons (urinary 1-hydroxypyrene-glucuronide) and aromatic amines (4-aminobiphenyl-hemoglobin adducts), as well as urinary mutagenicity, were measured in 47 healthy smokers and 50 non-smokers. DNA adducts were determined by P32-postlabeling in the exfoliated bladder cells of 39 healthy subjects. Both 1-hydroxypyrene-glucuronide (1-OHPG) and 4-aminobiphenyl adducts (4-ABP-Hb) were associated with smoking habits, but only 4-ABP-Hb adducts were associated with consumption of black, air-cured tobacco. The levels of 2 DNA adducts (numbers 2 and 4) in urothelial cells were clearly associated with 4-ABP-Hb adducts, in all subjects and in smokers. Levels of one of these DNA adducts (number 2) were also associated with 1-hydroxypyrene-glucuronide in urines, but in smokers the association was not statistically significant. Overall, these observations constitute further evidence of a role of arylamines in tobacco-induced bladder cancer. © 1996 Wiley-Liss, Inc.